The effect of beach volleyball training on muscle performance of indoor volleyball players - Balasas, D. G.; Christoulas, K.; Stefanidis, P.; Vamvakoudis, E.; Bampouras, T. M. (The Journal of Sports Medicine and Physical Fitness, 2018)
BACKGROUND: Beach volleyball is frequently used as a conditioning activity for indoor volleyball players, but little information exists regarding any performance benefits when transitioning from sand to hard court. The present study examined the effect of 12 weeks beach volleyball training on muscle performance of indoor volleyball players. METHODS: Eleven athletes who completed an indoor volleyball season and were willing to train and compete at beach volleyball, participated in the study. Muscle endurance of knee extensors and plantar flexors (torque at 120°/s following 40 contractions), muscle strength of knee extensors/ flexors (60, 180, 300°/s), dorsi/plantar flexors (torque at 60, 120, 180°/s) trunk flexors (60, 90, 180°/s) and power (squat [SJ] and countermovement [CMJ] jumps performed on sand and hard court surfaces) were assessed pre- and post-12 weeks of beach volleyball training. RESULTS: Knee extensors and plantar flexors endurance was higher post-12 weeks, as less torque decrease was found after 40 contractions for both muscle groups at post-12-week-time points. Knee extensors strength was higher post-12-weeks for 60 and 300°/s, while dorsi flexors strength was higher post-12 weeks for all speeds. SJ and CMJ vertical jump height was improved when measured on sand and on hard court. CONCLUSIONS: Twelve weeks of systematic training and competition at beach volleyball can improve muscular endurance of lower limbs and jumping height in indoor volleyball players. More importantly, these improvements are transferrable to hard court, making beach volleyball a very attractive alternative for conditioning indoor volleyball players during the off-indoor volleyball season.